2018
DOI: 10.1016/j.jco.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

A topological view on algebraic computation models

Abstract: We investigate the topological aspects of some algebraic computation models, in particular the BSS-model. Our results can be seen as bounds on how different BSS-computability and computability in the sense of computable analysis can be. The framework for this is Weihrauch reducibility. As a consequence of our characterizations, we establish that the solvability complexity index is (mostly) independent of the computational model, and that there thus is common ground in the study of non-computability between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 55 publications
0
47
0
Order By: Relevance
“…We also get an alternative proof of the following, which was previously shown in [24] using the squashing principle from [15]:…”
Section: Displacement Principle For Sort Kmentioning
confidence: 61%
See 1 more Smart Citation
“…We also get an alternative proof of the following, which was previously shown in [24] using the squashing principle from [15]:…”
Section: Displacement Principle For Sort Kmentioning
confidence: 61%
“…In [28] it is shown that Sort n+1 ≡ W Sort n ; it follows that Sort * ≡ W Sort * d ≡ W d∈N Sort d . The degree Sort * was shown in [24] to capture the strength of the strongly analytic machines [14,16], which in turn are an extension of the BSS-machines [1]. Sort is equivalent to Thomae's function; and to the translation of the standard representation of the reals into the continued fraction representation [30].…”
Section: The Principles Under Investigationmentioning
confidence: 99%
“…follows from arguments in Neumann and Pauly [34]. Since lim ≡ W lim, we can semidecide whether inf U d > 0 for all rational d in parallel, and this suffices to obtain inf{d…”
Section: Some Weihrauch Degrees Related To Hausdorff Dimensionmentioning
confidence: 99%
“…2 The Weihrauch degree corresponding to C N has received significant attention, e.g. in [3,4,6,7,[15][16][17][18][19]. In particular, as shown in [23], a function between computable Polish spaces is Weihrauch reducible to C N if and only if it is piecewise computable or equivalently is effectively 0 2 -measurable.…”
Section: Weihrauch Reducibilitymentioning
confidence: 99%
“…Now, LPO * corresponds to carrying out a fixed finite but arbitrary high number of equality tests on the real or complex numbers via the operator from [20]. The operator introduced in [17] captures using the given degree an arbitrary finite number of times (without the requirement that the number is fixed in advance), and it holds that [C N ] = LPO . Define one last operator on the Weihrauch degrees by setting [f ] := [f N ].…”
Section: Definitionmentioning
confidence: 99%